Roasting-leaching processes of gold-bearing minerals with cyanicidal metals - Lovera, Daniel Lovera (2002)
This research aims to explore possible solutions to the problems presented in auriferous sulfide minerals , which have cianicidas by metals ( Gold companions ) can not be cyanide by high reagent consumption , which makes the process uneconomical . Also be a problem hitting the small domestic mining sites that have these features that can not be traded concentrates by high penalties imposed on them , then creating a social problem that should be taken into account. At the experimental level by testing and subsequent acid leach cyanidation seek to find a process that allows for adequate separation of gold copper and other species also have high technical and economic efficiency. Exploratory tests shown indicate the feasibility of finding the right process for the investigated mineral content has Gold , chalcopyrite , malachite , magnetite , hematite , goethite , covellite , chalcocite , and marcasite . It seeks to find optimal process conditions , studying their phenomenology and suggesting a model that adequately explains the process and allow for simulations for different conditions , contrasting it with other developed models that posit other investigations.